2020
DOI: 10.1038/s41551-020-0549-2
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-binding IL-12 enhances tumour inflammation and drives the complete remission of established immunologically cold mouse tumours

Abstract: Checkpoint inhibitor (CPI) immunotherapy has achieved remarkable clinical success, yet its efficacy in 'immunologically cold' tumours has been modest. Interleukin (IL)-12 is a powerful cytokine that activates the innate and adaptive arms of the immune system, yet its administration has been associated with immune-related adverse events. Here, we show that the intravenous administration of a collagen-binding domain fused to IL-12 (CBD-IL-12) in mice bearing aggressive murine tumours accumulates in the tumour st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
132
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(142 citation statements)
references
References 50 publications
3
132
0
Order By: Relevance
“…Systemic (i.v.) administration of this CBD-IL12 was found to accumulate in EMT6 mammary carcinomas at significantly higher levels and induce higher rates of complete tumor regression against 1-week old B16F10 and EMT6 tumors compared to IL-12 ( 104 ). Inclusion of the CBD resulted in a 5–6-fold decrease in plasma half-life despite the larger size of CBD-IL12.…”
Section: Il-12 Delivery Strategiesmentioning
confidence: 89%
See 2 more Smart Citations
“…Systemic (i.v.) administration of this CBD-IL12 was found to accumulate in EMT6 mammary carcinomas at significantly higher levels and induce higher rates of complete tumor regression against 1-week old B16F10 and EMT6 tumors compared to IL-12 ( 104 ). Inclusion of the CBD resulted in a 5–6-fold decrease in plasma half-life despite the larger size of CBD-IL12.…”
Section: Il-12 Delivery Strategiesmentioning
confidence: 89%
“…injection were surprisingly similar although typical sites of collagen targeted drugs, e.g., bone and skin, were not examined. Most importantly, although elevated liver enzymes were observed, levels following CBD-IL12 at an impressive dose of 50μg/mouse were similar to 10μg/mouse of IL-12 ( 104 ).…”
Section: Il-12 Delivery Strategiesmentioning
confidence: 91%
See 1 more Smart Citation
“…We 22 and others previously found that IL-12 can improve cancer immune elimination via enhanced CD8 + T cell proliferation, 24 cytotoxicity, 17, 25 survival, 17 and T cell receptor (TCR) signaling. 26,27 As clinically approved T cell engager therapies are thought to act primarily on a subset of CD8 + T cells, 28,29 we posited that IL-12 may improve the lytic activity of blinatumomab which bi-specifically targets T cell CD3 and leukemic B cell CD19.…”
Section: Il-12 Enhances Bispecific T Cell Engager Activitymentioning
confidence: 91%
“…Interleukin 12 (IL-12) increased intratumoral inflammation and improved checkpoint blockade immunotherapy in a mouse model of melanoma. 5 The recombinant cytokine was fused to a collagen-binding domain, which targets the exposed collagen in the leaky vasculature in the tumor. The combination with a checkpoint inhibitor eradicated large tumors in the experimental animals.…”
Section: Recombinant Il-12 Enhances Immunotherapymentioning
confidence: 99%